Gwarowy obraz rodzeństwa .......... 609 - Tyrpa, Anna (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
A DIALECTAL IMAGE OF SIBLINGSAn analysis of dialectal material concerning siblings (lexemes: rodzeństwo [‘sibling’], brat [‘brother’], siostra [‘sister’], together with their derivatives and phrasemes) has led to the formulation of the following points: 1. Siblings are good for each other; 2. Brothers and sisters are close to one another; 3. Brothers are equal to each other; 4. Brothers and sisters are similar to one another; 5. Older brother is bigger, younger brother is smaller; 6. Brother-in-law is a brother, sisterin- law is a sister; 7. Brother and sister cannot marry one another; 8. Best man is a brother, bridesmaid is a sister; 9. Male friend is a brother, female friend is a sister; 10. Man is a brother; 11. My brother! – to a man, my sister! – to a woman; 12. Monk is a brother, nun is a sister; 13. Nurse is a sister.